Field trial of Provus-Alkin-amalgamation evaluation application based on Weighted-Product-Rwa-Bhineda mods - Suyasa, P. Wayan Arta; Divayana, Dewa Gede Hendra; Ariawan, I Putu Wisna; Andayani, Made Susi Lissia; Wiradika, I Nyoman Indhi; Adiarta, Agus (Journal of Education and Learning (EduLearn), 2025)
The purpose of this study was to demonstrate the effectiveness level of the Provus-Alkin-amalgamation evaluation application based on Weighted-Product-Rwa-Bhineda modification through the results of field trials. This evaluation application was an evaluation tool formed by a combination of educational evaluation models (Provus model and Alkin model), decision support system methods (weighted product), and the concept of Balinese local wisdom (Rwa Bhineda). This research approach was developed, using the Borg and Gall model. The focus of the development phase in this study was field trials and revisions to field trials. The tool used to provide scores by respondents in field trials was a questionnaire. Subjects involved in field trials were 164 respondents. The research location was at several IT vocational schools in Bali. Data analysis was done by comparing the results of field trials with effectiveness standards referring to a five scale. The results showed that the percentage of effectiveness was 81.20%. It proved that the Provus-Alkin-amalgamation evaluation application based on Weighted-Product-Rwa-Bhineda modification was good. The impact of the results of this research is as a trigger to develop innovations in educational evaluation by integrating various fields of science (multidisciplinary science) in the form of one digital application.